Novel evidence of team reasoning in spatially-framed experimental bargaining games - Andrea Isoni; Andrea Isoni; Anders Poulsen; Robert Sugden; Kei Tsutsui (Frontiers in Behavioral Economics)
IntroductionTeam reasoning and bounded best-response models have been used to explain coordination success and failure in games with focal points. Most attempts at discriminating between them have used games framed as matching problems in which players choose between alternative payoff distributions. But evidence suggests that coordination failures are less dramatic in games framed as bargaining problems in which players separately claim parts of a valuable surplus. We contrast team reasoning and bounded best-response models using a variant of an established experimental paradigm in which tacit bargaining games are given a spatial frame.MethodsParticipants (N = 100) took part in 24 one-shot spatially-framed bargaining games in which the total surplus was divided into two, four or eight valuable discs scattered on a grid where each player was located in a specific position. Twelve games had spatial cues suggesting a Least Unequal Efficient (LUE) surplus allocation in which each player claimed the discs closest to them, and 12 games had no such cues. Each player's payoff was the total value of the discs claimed by them but not by the other player. In this setup, bounded best-response models predict players would follow the dominant strategy of claiming all discs, while team reasoning predicts each player should claim one of the LUE shares.ResultsAcross all games, the proportion of players claiming all discs ranged from 35 to 63%, exceeding 50% in just 4 games. In line with team reasoning, most non-dominant claims were LUE shares and players were significantly more likely to claim near than far discs.DiscussionExploiting spatial framing and leveraging payoff dominance, our experiment provides novel evidence for team reasoning in tacit bargaining. We also find some evidence that players favored by spatial cues sometimes do not accept that advantage. We discuss possible explanations for these patterns.